On the Interpretation of Religious Freedom: A Conversation with Ronald Dworkin - Gamwell, Franklin I. (The journal of religion, 2015)
This article focuses on Ronald Dworkin, an American philosopher and scholar of U.S. constitutional law and jurisprudence. Topics discussed include Dworkin's death in 2013, his moral, political and legal theories, and his books, including "Is Democracy Possible Here?" "Justice for Hedgehogs," and "Religion without God." Also mentioned are Dworkin's interpretation of the religion clauses initiating the U.S. Constitution's First Amendment as well as of morality and ethics.